Analisis Kemampuan Berpikir Kritis Siswa Ditinjau dari Perbedaan Gender pada Siswa Kelas X, XI MIPA SMA Negeri 1 Kayangan Tahun Pelajaran 2021/2022 - Yuniar, Sonia Rega; Masjudin, Masjudin; Yulianti, sri (Universitas Pendidikan Mandalika (UNDIKMA), 2022)
This study aims to describe students' critical thinking skills in terms of gender differences in class X, XI MIPA students of SMA Negeri 1 Kayangan. This type of research is qualitative descriptive research. The subjects of the study totaled 18 people, which consisted of subjects on a gender perspective selected based on the results of previously implemented tests, namely 6 people for the gender perspective. Data were collected through test results of critical thinking skills as well as interview results as a follow-up to deepen the findings obtained from the test results. The results of this study showed that for critical thinking ability in terms of gender in the high category showed that for L1 subjects did not meet the self-regulation indicators and P1 subjects met all indicators. In the medium category it is shown that for subjects L2 does not meet on the analysis indicators whereas the P2 subjects do not meet on the interpretation and analysis indicators. In the low category it shows that neither the L3 subject nor the P3 subject meets all indicators. Based on the results of the study, it can be concluded that when viewed from a gender perspective, the ability to think krtitis between male and female subjects does not show significantly where the difference in critical thinking ability lies.